Technological Embodiment and the Fragmentation of Social Identity in the Era of Human Enhancement - Abror, Sirojuddin; Khayru, Rafadi Khan; Chasanah, Uswatun; Issalillah, Fayola (Bulletin of Science, Technology and Society, 2025)
This study explores how biohacking technologies, particularly those involving cognitive augmentation and bodily modification, reshape social identity and class structures through a post-humanist sociological perspective. By employing a literature-based approach, the research analyzes how technological interventions alter the construction of the self, redefine social hierarchies, and fragment traditional identity categories. The analysis reveals that biohacking introduces new symbolic economies wherein enhanced bodies become markers of social privilege. Access to enhancement tools remains uneven, further embedding socio-economic disparities. Technologically modified individuals often experience elevated status, while those without access face exclusion from evolving social norms. The concept of identity is transformed into a dynamic construct shaped by technological capability, leading to the emergence of techno-subjectivities. These shifts challenge the integrity of communal experiences and disrupt the formation of collective solidarity. The findings suggest that biohacking, while presented as a personal or liberatory choice, contributes to the reproduction of structural inequality when left unregulated. The study underscores the importance of critical inquiry into how identity and class are continually reconfigured in light of technological advancement, offering a sociological contribution that moves beyond celebration toward deeper reflection.